Real-world effects of hyoscine butylbromide combined with paracetamol in women with dysmenorrhea: a patient survey - Kathrin Stewen; Selina Miehle; Harald Weigmann; Roxana Schwab (Frontiers in Medicine)
IntroductionDysmenorrhea symptoms are frequent and often self-treated using non-prescription medicines.MethodsTo further characterize women with dysmenorrhea using a combination of hyoscine butylbromide plus paracetamol (PLUS) for self-management of their complaints, we performed a secondary analysis of a published pharmacy-based patient survey.ResultsA total of 314 women (mean age: 32.3 years) with dysmenorrhea reported a pain and cramps intensity of 7.45 ± 2.13 (means ± SD) on a 0–10 Likert scale, which was reduced to 2.86 ± 1.81 upon treatment. Associated impairments of work/daily chores, leisure activities, and sleep were improved by 64.6, 62.2, and 70.4%, respectively. The onset of symptom relief was within 60 min in 84.7%. Tolerability was rated as very good or good by 97.2%; 82.8% were repeat users, 97.5% reported their intention to purchase the product again, and 97.1% reported their intention to recommend it to relatives, friends, and colleagues.DiscussionThese findings confirm the efficacy and tolerability data on PLUS from randomized controlled trials in a larger group of women conducting self-management of their dysmenorrhea in a real-world setting. Future studies should compare PLUS to other non-prescription treatments.